BEREBUT â€œBERKAHâ€ SENDANG SELIRANG DALAM PERSPEKTIF BEBERAPA KOMUNITAS MASYARAKAT MUSLIM KOTA GEDE, YOGYAKARTA: Sebuah Upaya Mempromosikan Dialog Agama dan Budaya - waryono waryono (Jurnal Masyarakat dan Budaya, 2017)
This article discusses about cultural phenomenon called by sendang selirang. Sendang Seliran is the name of one of the local culture typical in Kota Gede Yogyakarta, which are still preserved. Sendang Seliran is a tradition of cleaning the pool in the former kingdom of Mataram environment early in Kota Gede. The tradition interpreted differently by the three groups in Kota Gede: Abangan, muslim students, and intellectual. The problem is the background why and what are the differences? Although different, why citizens of Kota Gede, remain in harmony? This paper departs from the framework developed by Clifford Geertz interpretive ethnography to understand a cultural event that occurs in the community. The results show that for people Abangan, Sendang Selirang are rites and ceremonies performed with religious emotion and have sacred properties. Turned out to be different meanings for groups of students who are represented by Muhammadiyah. For some activists Muhammadiyah, tradition nawu Sendang (Sendang Selirang) is part of superstition, heresy, and kurafat, so it should be avoided. As for the "intellectuals", the event is not enough nawu sendang viewed from the side of religion, but also in terms of culture. This is a "middle way" to mediate the two previous groups of potential conflict. Evidence suggests that differences in the views of the three groups is not only influenced by their religious views, but also by other factors outside the religion, such as equity in the administration and material benefits. Nevertheless, unity in difference remains the preferred, so that the harmony continues to perform well. Artikel ini membahas tentang fenomena budaya lokal Sendang Selirang. Sendang Selirang merupakan tradisi membersihkan kolam yang berada di bekas lingkungan Kerajaan Mataram Awal di Kota Gede. Tradisi tersebut dimaknai secara berbeda oleh tiga kelompok di Kota Gede, yaitu kelompok Abangan, Santri, dan Intelektual. Permasalahannya, mengapa dan apa latar belakang perbedaannya? Meskipun berbeda, mengapa warga Kota Gede tetap harmonis? Penelitian etnografi dengan wawancara mendalam dan observasi ini telah menemukan bahwa bagi masyarakat Abangan, Sendang Selirang merupakan ritus dan upacara yang dilaksanakan dengan emosi keagamaan dan mempunyai sifat keramat. Pemaknaan ini berbeda dengan kelompok santri yang direpresentasikan oleh Muhammadiyah. Oleh beberapa aktivis Muhammadiyah, ritual ini dianggap sebagai bagian dari takhayul, bidâ€™ah, dan kurafat, sehingga harus dihindari. Sementara itu, bagi kelompok intelektual, peristiwa nawu sendang tidak cukup dipandang dari sisi agama, melainkan juga perlu dilihat dari sisi budaya. Hal itu merupakan â€œjalan tengahâ€ untuk menengahi dua kelompok sebelumnya dan menghindari terjadinya potensi konflik.